Hand dermatitis: A comprehensive review with special emphasis on COVID-19 pandemic - Ziaul Haque Ahmed; Komal Agarwal; Rashmi Sarkar (Wolters Kluwer Medknow Publications, 2021)
Hand dermatitis (HD) is a chronic, relapsing, and remitting inflammatory condition that adversely affects the quality of life of the individual and gravely impacts the mental and socioeconomic well-being by causing professional hindrance and often leading to loss of wages. Despite being one of the most common skin conditions seen by dermatologists, it is often underreported. With the coronavirus pandemic ongoing, there is an emphasis on hand hygiene-being a widely publicized and important preventive measure to control the spread of the Coronavirus disease (COVID-19) virus. Emphasis on hand hygiene has led to a surge in HD, and the presence of HD, in turn, leads to compromised hand hygiene practices and this breach in the skin barrier contributes to another portal of entry of infective agents. We undertook a comprehensive English literature search across multiple databases such as PubMed, SCOPUS, EMBASE, MEDLINE, and Cochrane using keywords and MeSH items to obtain and review several relevant articles. Thus, this review focuses on various clinical, diagnostic as well as therapeutic aspects of this much prevalent and debilitating skin condition which deserves more attention especially during the times of the COVID-19 pandemic where the utmost emphasis is being given to handwashing leading to a vicious cycle of a surge in the cases of HD and compromised skin barrier causing increased susceptibility to the COVID-19 infection.